Human Resource Development Strategy As Preparation For The Industrial Revolution Era 5.0 - Ade Octaviany, Rini; Sihotang, Winda; Sanjaya Simarmata, Petrus; Rahman, Arif; Muliati, Agustina (CV. Inara, 2022)
This study aims to describe the Human Resource Development strategy as preparation for the Industrial Revolution Era 5.0. In the 5.0 era, the industry began to touch the virtual world, in the form of human, machine and data connectivity, all of which are already everywhere, known as the Internet of Things (IoT). Therefore, the Human Resource Development Strategy needs to be considered considering that Indonesia is a country with a high number of productive ages. This research uses descriptive qualitative research. In qualitative research, the formulation of the problem taken from the case study that will be examined in this context is the HR Development Strategy as Preparation for the Industrial Revolution Era 5.0. Qualitative data was collected by means of interviews, document analysis, literature study and direct observation. There are several methods of developing Human Resources that can be done, namely: 1) Skill Training Method; 2) Retraining Methods; 3) Cross-Functional Training Methods; 4) Team Training Methods; 5) Creativity Training Method. Curriculum development is also one of the things that can direct and shape the character of Indonesian people to be ready to face the industrial revolution 5.0.